2019
DOI: 10.1021/acs.orglett.9b02314
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphine-Catalyzed Difluoroalkylation of Alkenes

Abstract: Atom transfer radical addition and Heck-type reaction between alkenes and ethyl iododifluoroacetate by using organophosphine compounds as catalysts have been developed. The reaction proceeds under mild reaction conditions with excellent functional group tolerance and high chemo-and regioselectivities. Mechanistic study indicates that the reaction might be initiated via noncovalent interactions between an organophosphine catalyst and a carbon−iodine bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…In the latter case, the formation of a halogen bond between the electron-deficient perfluoroalkyl iodide and a suitable Lewis base results in homolytic bond cleavage upon irradiation of visible light. Amines [28][29][30][31][32][33], phenols [34], ketones [35,36], as well as phosphines [37][38][39][40][41] have been reported for this purpose in either stoichiometric or catalytic quantities.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case, the formation of a halogen bond between the electron-deficient perfluoroalkyl iodide and a suitable Lewis base results in homolytic bond cleavage upon irradiation of visible light. Amines [28][29][30][31][32][33], phenols [34], ketones [35,36], as well as phosphines [37][38][39][40][41] have been reported for this purpose in either stoichiometric or catalytic quantities.…”
Section: Introductionmentioning
confidence: 99%
“…However, the transformation of demanding alkenes or terminal alkynes was not substantially improved. Only in the case of phenylacetylene (Table 1, entry 4) a better yield was obtained by by changing the Lewis acid from B(C 6 F 5 ) 3 (2) to B(2,6-F 2 C 6 H 3 ) 3 (21). With respect to the phosphine catalyst partner, we found that only t Bu 3 P (1) promoted the reaction efficiently.…”
Section: Scheme 5 Flp-catalyzed Iodoperfluoroalkylation Of Alkenes Inmentioning
confidence: 87%
“…27 We assumed that this formation of a stable [ t Bu 3 PH][PhC≡CB(C 6 F 5 )] intermediate might be a faster and more efficient process than the iodoperfluoroalkylation of the alkyne. To overcome this problem of potential catalyst deactivation and potentially improving tolerance towards heteroatoms, electronically tuned boranes such as tris(2,6-difluorophenyl)borane (21) and the more water-stable (2,3,6-trichlorophenyl)bis(2,3,6trifluorophenyl)borane (22) were investigated ( Table 1 and Table 2). However, the transformation of demanding alkenes or terminal alkynes was not substantially improved.…”
Section: Scheme 5 Flp-catalyzed Iodoperfluoroalkylation Of Alkenes Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, non-covalent interaction initiated fluoroalkylation reaction has emerged as an attractive strategy [37][38][39][40][41][42][43][44][45][46][47]. Inspired by our previous studies in this field [48][49][50][51], we envision that if the solvent can serve as an electron donor compound, the reactions would be simpler. Here, we demonstrate a…”
Section: Introductionmentioning
confidence: 99%